Longitudinal panretinal microaneurysm dynamics on ultra-widefield fluorescein angiography in eyes treated with intravitreal aflibercept for proliferative diabetic retinopathy in the recovery study. Issue 8 (22nd August 2020) - Babiuch, Amy; Wykoff, Charles Clifton; Hach, Jenna; Srivastava, Sunil; Talcott, Katherine E; Yu, Hannah J; Nittala, Muneeswar; Sadda, SriniVas; Ip, Michael S; Le, Thuy; Hu, Ming; Reese, Jamie; et al.
Abstract : Background/Aims: Quantifying microaneurysms (MAs) turnover may be an objective measure for therapeutic response in diabetic retinopathy. This study assesses changes in MA counts on ultra-widefield fluorescein angiography (UWFA) in subjects undergoing treatment with intravitreal aflibercept injection (IAI) for proliferative diabetic retinopathy (PDR) in the Intravitre al Afliberc ept for Retinal No n-Perfusion in Proliferativ e Diabe tic R etinopathy (RECOVERY) study using an automated MA detection platform. Methods: RECOVERY is a prospective study that enrolled 40 subjects with PDR randomised 1:1 to receive 2 mg IAI every 4 weeks(q4wk) or every 12 weeks (q12wk). UWFA images were obtained at baseline, 6 months and 1 year. Images were analysed using an automated segmentation platform to detect and quantify MAs. Zones 1, 2 and 3 correspond to the macula, mid-periphery and far-periphery, respectively. Results: The q4wk cohort demonstrated a significant decline in MAs in all zones and panretinally at baseline versus month 6, baseline versus year 1, and month 6 versus year 1 (−20.0% to −61.8%; all p<0.001). In the q12wk cohort, baseline versus month 6 showed a significant decline panretinally (mean: −34.2%; p<0.001) and in zone 3 (mean −44.18%; p<0.001). Addiitonally, baseline to year 1 in the q12wk group demonstrated significant decline panretinally (mean: −47.7%; p<0.001) and in zone 3 (mean: −59.8%; p<0.001). All zones demonstrated significantly decline from month 6 to year 1 in the q12wk group. Conclusion: Therapy with IAI demonstrates significantly reduced panretinal MA counts in PDR at 1 year in both treatment groups. The use of automated platforms to detect and quantify MAs may provide a novel imaging marker for evaluating disease activity and therapeutic impact. Trial registration number: NCT02863354.